JAMES: An object‐oriented Java framework for discrete optimization using local search metaheuristics - De Beukelaer, Herman; Davenport, Guy F.; De Meyer, Geert; Fack, Veerle (Software, practice & experience, 2017)
Summary This paper describes the Java Metaheuristics Search framework (JAMES, v1.1): an object‐oriented Java framework for discrete optimization using local search algorithms that exploits the generality of such metaheuristics by clearly separating search implementation and application from problem specification. A wide range of generic local searches are provided, including (stochastic) hill climbing, tabu search, variable neighbourhood search and parallel tempering. These can be applied to any user‐defined problem by plugging in a custom neighbourhood for the corresponding solution type. Using an automated analysis workflow, the performance of different search algorithms can be compared in order to select an appropriate optimization strategy. Implementations of specific components are included for subset selection, such as a predefined solution type, generic problem definition and several subset neighbourhoods used to modify the set of selected items. Additional components for other types of problems (e.g. permutation problems) are provided through an extensions module which also includes the analysis workflow. In comparison with existing Java metaheuristics frameworks that mainly focus on population‐based algorithms, JAMES has a much lower memory footprint and promotes efficient application of local searches by taking full advantage of move‐based evaluation. Releases of JAMES are deployed to the Maven Central Repository so that the framework can easily be included as a dependency in other Java applications. The project is fully open source and hosted on GitHub. More information can be found at http://www.jamesframework.org. Copyright © 2016 John Wiley & Sons, Ltd.